The Impact of Vascular Risk Factors on Post-stroke Cognitive Impairment: The Nor-COAST Study - Aam, Stina; Gynnild, Mari Nordbø; Munthe-Kaas, Ragnhild; Saltvedt, Ingvild; Lydersen, Stian; Knapskog, Anne-Brita; Ihle-Hansen, Hege; Ellekjær, Hanne; Eldholm, Rannveig Sakshaug; Fure, Brynjar (Frontiers in Neurology, 2021)
Introduction: Post-stroke cognitive impairment (PSCI) is common, but evidence on the impact of vascular risk factors is lacking. We explored the association between pre-stroke vascular risk factors and PSCI and studied the course of PSCI. Materials and methods: Vascular risk factors were collected at baseline in stroke survivors (n=635). Cognitive assessments of attention, executive function, memory, language, and the Montreal Cognitive Assessment (MoCA) were performed at three and/or 18 months post-stroke. Stroke severity was assessed with the National Institutes of Health Stroke Scale (NIHSS). PSCI was measured with global z; MoCA z-score; and z-score of the four assessed cognitive domains. Mixed-effects linear regression was applied with global z, MoCA z-score, and z-scores of the cognitive domains as dependent variables. Independent variables were the vascular risk factors, time, and the interaction between these. The analyses were adjusted for age, education, and sex. Results: Mean age was 71.6 years (SD 11.7), 42 % were females and mean NIHSS score at admittance was 3.8 (SD 4.8). Regardless of vascular risk factors, global z, MoCA and all the assessed cognitive domains were impaired at three and 18 months, with MoCA being the most severely impaired. Atrial fibrillation (AF) was associated with poorer language at 18 months and coronary heart disease (CHD) with poorer MoCA at 18 months (LR=12.80, p=0.002, and LR=8.32, p=0.004, respectively). Previous stroke was associated with poorer global z and attention at three and 18 months (LR=15.46, p<0.001, and LR=16.20, p<0.001). In patients without AF, attention improved from three to 18 months, and in patients without CHD, executive function improved from three to 18 months (LR=10.42, p<0.001, and LR=9.33, p=0.009, respectively). Discussion: Our findings indicate that a focal stroke lesion may initiate pathophysiological processes leading to global cognitive impairment. The poorer prognosis of PSCI in patients with vascular risk factors emphasizes the need for further research on complex vascular risk factor interventions to prevent PSCI.